EVALUATION OF SOME CHARACTERISTICS ON THE CARCASS OF BOVINES AND BUFFALOES - Neto, Otavio Cabral (2010)
ABSTRACT. Neto O.C., Rodrigues V.C., Costa D.P.B. da, Medeiros L.F.D., Vieira D.H., Camargo A.M. & Pádua F.T. de. [Evaluation of some characteristics on the carcass of bovines and buffaloes]. Avaliação de algumas características da carcaça de bovinos e bubalinos. Revista Brasileira de Medicina Veterinária, 32(3):151-160, 2010. Faculdade de Ciências Agro-Ambientais da Sociedade Nacional de Agricultura, FAGRAM/SNA. Avenida Brasil, 9727, Olaria, Rio de Janeiro, RJ 21040-360, Brasil. E-mail: tavicocabral@hotmail.com The objective of this study was to evaluate some characteristics measure by ultrasound in live animals and with scale in the carcass of Sindhi bovines and Mediterranean buffaloes, finished in feedlot. The animals were slaughtered when they reached the average body weight of 488.3 ± 8.94 kg for Sindhi and 492.5 ± 8.61 kg for Mediterranean. The experimental design was the completely randomized. There was no difference between genetic groups for rib eye area (REA) measured by ultrasound. However, there was significant difference for fat thickness (FT), fat thickness in the cup of rump and marbling. Bovine group showed lower averages (5.3 vs 7.7 mm and 5.4 vs 8.0 mm) for fat thickness and fat thickness in the cup of rump, respectively, while for marbling, bovines presented higher values (9.7 vs 5.9 points). There was no significant difference for REA and FT obtained in the carcass, as well as to the ratio of muscle, bone and fat. The correlations between REA and FT obtained by ultra-sound and measured in the carcass were positives and significant (0.68 and 0.55 to the first and second characteristic, respectively). Ultrasound measurements are correlated to measurements measured on carcass of steers finished in feedlot. The carcass from both groups presents similar quality observed among the majority of studied characteristics. However, considering the marbling grade an indicative of intramuscular fat, the buffalo’s meat can be considered healthier for human intake.